Traditional knowledge of fisher folk of Kollam district, Kerala on coastal and marine biodiversity and conservation - Biju Kumar, A.; Anitha, R. (Journal of Traditional and Folk Practices (JTFP), 2017)
The fisheries sector in Kerala state of India is particularly rich in custom, tradition and local knowledge, reflecting this in its communities, their established beliefs and practices. The proximity to the natural resource base has a dominating influence on the culture and thinking of the fishing community. This paper documents the traditional knowledge of traditional fishermen in Kollam district of Kerala on marine biodiversity and conservation, based on a questionnaire survey conducted in 17 fishing villages. The paper records traditional knowledge of fisher folk on algal blooms, jellyfish blooms, coastal vegetation, sea snakes, sea turtles, whales, dolphins, sea birds, reefs in the sea, seasonal availability and medicinal importance of fishes, identification of fish in the sea, threats to marine biodiversity, and their perceptions on conservation and management. For the conservation and sustainability of bioresources, traditional fishers demand increase in the number of monsoon trawl ban days and implementation of the ban in two times a year based on the breeding time of fishes. Further, for ensuring sustainability they suggested limits to exploitation and preventing destructive fishing practices. This knowledge can be further